Determinan Dan Pola Konsumsi Antibiotik Pada Balita Dengan Diare di Indonesia: Analisis Data Demographic Health Survey 2017 - Tashya Dhela Maylinda; Rivai Endra Dwi Yulianto (Universitas 17 Agustus 1945 Jakarta, 2025)
Diarrhea is still the second leading cause of death for children under five years of age. Deaths of children under five years due to diarrhea are caused by unsafe water, inadequate sanitation, and hygiene. Socio-demographic characteristics, environment, behavior, and parenting practices are factors associated with diarrhea in children under five years in Indonesia. The use of antibiotics in the treatment of diarrhea needs more attention. Antibiotic resistance can occur if its use is not based on a proper diagnosis. This study was conducted to examine the factors that influence the incidence of diarrhea in children under five years of age. This study also looked at the prevalence of treatment centers for diarrhea patients and the use of antibiotics for the treatment of diarrhea in children under five years of age. The data used is cross-sectional data on children under five living in households in Indonesia taken from the 2017 DHS survey through data collections and survey reports. Descriptive analyzes were performed on survey reports and datasets related to demographics, the prevalence of diarrheal diseases, and the use of antibiotics for the treatment of diarrhea. Significance analysis was conducted to see whether the selected variables had an effect on the incidence of diarrhea in children under five years of age. Gender, age, location of residence (urban or rural), wealth level, mother's education level and the main material of the house floor are significant factors influencing the incidence of diarrhea in children under five years. Puskesmas is a place to seek treatment for diarrhea which is most frequently visited by children under five years old (20.99%). 10.9% of pediatric patients with diarrhea visited more than one health facility. Private hospitals are the places that most often give antibiotics to children under five years of age who have diarrhea (25%). Antibiotics were given not only by licensed health care facilities but also by other places visited by respondents, namely traditional birth attendants, grocery stores, and other sources.